Finnish case–control and family studies support PTPN22 R620W polymorphism as a risk factor in rheumatoid arthritis, but suggest only minimal or no effect in juvenile idiopathic arthritis - Seldin, M F; Shigeta, R; Laiho, K; Li, H; Saila, H; Savolainen, A; Leirisalo-Repo, M; Aho, K; Tuomilehto-Wolf, E; Kaarela, K; Kauppi, M; Alexander, H C; et al. (Genes and immunity, 2005)
Several studies have identified the PTPN22 allelic variant 1858 C/T that encodes the R620W amino-acid change as a putative susceptibility factor in autoimmune diseases. The current study was undertaken to examine a large cohort of Finnish rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA) subjects using both population control and, importantly, family-based association methods. The latter is particularly important when, as is the case for the 1858 C/T polymorphism, the frequency of the variant allele (T) differs in both major ancestral populations and in subpopulations. The analysis of rheumatoid factor-positive 1030 RA probands from Finland provides strong support for association of this variant in both population studies (allele specific odds ratio (OR)=1.47, 95% confidence interval (CI)=1.27–1.70, P =3 × 10 −7 ) and in family studies ( P <10 −6 ). In contrast, no allelic association was seen with JIA (230 probands) and only weak evidence for a genotypic effect of 1858T homozygotes was observed in this population.